Negative regulation of the major histocompatibility complex class I enhancer in adenovirus type 12-transformed cells via a retinoic acid response element. - Kralli, A (1992)
In cells transformed by the highly oncogenic adenovirus type 12 (Ad12), the viral E1A proteins mediate transcriptional repression of the major histocompatibility class I genes. In contrast, class I transcription is not reduced in cells transformed by the nononcogenic Ad5. The decreased rate of class I transcription is, at least in part, the result of a reduced major histocompatibility complex class I enhancer activity in Ad12-transformed cells and correlates with an increase in the levels of a DNA-binding activity to the R2 element of the enhancer (R. Ge, A. Kralli, R. Weinmann, and R. P. Ricciardi, J. Virol. 66:6969-6978, 1992). Employing transient transfection assays, we now provide direct evidence that the R2 element can confer repression in Ad12- but not Ad5-transformed cells. Repression by R2 was observed only in the presence of the positive enhancer element R1 and was dependent on (i) the number of the R2 elements and (ii) the relative arrangement of R2 and R1 elements. The putative R2-binding repressor protein, R2BF, was similar in molecular weight and binding specificity to members of the thyroid hormone/retinoic acid (RA) receptor family. RA treatment abrogated the R2-mediated repression in Ad12-transformed cells and had no effect on the activity of R2/R1-containing promoters in Ad5-transformed cells. These results are consistent with the presence of an R2-binding repressor in Ad12-transformed cells. In the absence of RA, the repressor compromises enhancer activity by interfering with the activity of the positive cis element R1. RA treatment of Ad12-transformed cells may render the repressor inactive.